The killing edge - Graham, Heather (Don Mills, Ont. : MIRA Books, 2010)
Florida psychologist Chloe Marin and Luke Cane, a British ex-cop-turned-P.I. investigating the disappearance of a young swimsuit model on behalf of her father, have trouble trusting each other, even though they are attracted to one another and have the same hunch that a killer is using a modeling agency to stalk his prey. When Chloe arrives late for an appointment at the modeling agency, she discovers a gruesome mass murder eerily similar to one she witnessed a decade ago--and she's afraid she's the target.
Keywords: Mass murder -- Fiction; Missing persons -- Fiction; Private investigators -- Fiction; Women psychologists -- Fiction; Florida -- Fiction; Mystery fiction; Romantic suspense fiction